Nitrogen transforming organisms in some forest soils of Chittagong University camputs - Chowdhury, N; Islam, MS; Osman, KT (Chittagong University Journal of Biological Sciences, 2013)
Association of nitrogen transforming bacteria in soils under six-forest tree plantations viz. Lagerstroemia speciosa, Acacia auriculiformis, Acacia mangium, Dipterocarpus turbinatus, Tectona grandis, and Eucalyptus camaldulensis were assessed in the present study. Azotobacter population was the least among the nitrogen-transforming bacteria in all soils. Soils under L. speciosa had the lowest population of ammonifying, Nitrosomonas, Nitrobacter and denitrifying bacteria and A. auriculiformis had higher average MPN values, although E. camaldulensis had the highest Nitrobacter population. Population of the microorganisms was positively and significantly correlated with each other, except Azotobacter. Azotobacter was only significantly correlated with the denitrifying bacteria. The nitrogen-transforming microorganisms were significantly related with the total nitrogen content and pH of the forest soils. DOI: http://dx.doi.org/10.3329/cujbs.v3i1.13413 The Chittagong Univ. J. B. Sci.,Vol. 3(1&2):127-138, 2008